PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, KUALITAS PELAYANAN DAN EKSPEKTASI KINERJA TERHADAP KEPUASAN PENGGUNA DALAM PENERAPAN SISTEM TEKNOLOGI INFORMASI PADA KOPERASI DI KOTA PEMATANGSIANTAR - Dedi Suhendro (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2016)
The objective of the research was to find out the influence of independet variables (the variable of system quality the variable of information quality, the variable of service quality, and the variable of performance expectancy) simultaneously and partially had the influence on dependent variable (users’ satisfaction). The population was 300 cooperatives at Pematangsiantar, and 225 of them were used as the samples, taken by using purposive sampling technique. The data were processed by using multiple linier regression analysis with an SPSS software program. The result of the hypothesis showed that independent variables (the variable of system quality, the variable of information quality, the variable of service quality and the variable of performance expectation) simultaneously had significant influence on dependent variable (the variable of users’ satisfaction) at the cooperatives, Pematangsiantar. Partially, the variable of system quality, the variable of service quality and the variable of performance expectation had positive and significant influence on user’s satisfaction at the cooperatives, Pematangsiantar, but the variable of information quality did no have any influence on users’ satisfaction at the cooperative, Pematangsiantar